A rare case report: concurrent COVID-19 and acute cerebrovascular ischemic stroke in a patient with Sheehan's syndrome - Deniz Çekiç; Kubilay Işsever; Selçuk Yaylacı; Didar Şenocak; Sümeyye Çekiç; Ilhan Yıldırım; Mehmet Halil Öztürk; Oğuz Karabay (National Scientific Medical Center, 2021)
Introduction: SARS-Corona Virus-2 (SARS-CoV-2/COVID-19) is a novel member of coronaviridae family. This new disease first appeared in China in December 2019, and can cause severe respiratory failure in advanced cases. COVID-19 was announced as a pandemic in March 2020 by WHO. It has infected 76 million people and has caused the death of more than 1.5 million people until December 2020. Common symptoms of this disease are mostly fever, cough, shortness of breath, anosmia, and fatigue. But atypical presentations have also being reported. Here, we present a COVID-19 patient with an unusual neurological symptom. Case: 82-years-old female patient with a history of hypertension and Sheehan's syndrome came to the emergency room with the complaint of fever, shortness of breath and left hemiplegia. Although nasopharyngeal swab PCR test was negative (twice), acute phase reactants were elevated and chest CT revealed typical findings of COVID-19 pneumonia, so the patient was diagnosed as COVID-19. Since the patient had left hemiplegia, a cranial CT and diffusion-weighted MRI were performed to see whether a central neurological pathology was present. Both imaging revealed the findings of acute ischemic stroke (AIS). Afterwards, the patients was hospitalized and was started on Hydroxychloroquine, acetylsalicylic acid (ASA), favipiravir and methylprednisolone. At the 7th day of follow up, the nasopharyngeal swab PCR test was reperformed and found as positive. On the 10th day of treatment, the symptoms and acute phase reactants regressed. Left hemiplegia of the patient also regressed and she was discharged from the hospital at the 12th day of admission without a sequelae. Discussion and conclusion: Since there has been a recent evidence of strong relationship between COVID-19 and acute ischemic pathologies due to pathophysiology of COVID-19, we should be suspicious of acute ischemic stroke in a COVID-19 patient with neurological symptoms, especially when the patient had a history like Sheehan's Syndrome disease  may aggravate or hide the symptoms.